Wielozawodowość ludności rolniczej w RFN i Polsce - Mossakowska, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1995)
This is a presentation of causes and range of the phenomenon of multivocationality in agriculture in Germany and Poland. Multivocationality means being a farmer and having another work done against compensations. The reasons for such work both in Germany and Poland are similar. They have an economical character and are mainly due to: too low agricultural income and free unused work resources on farms. This multivocationality in German agriculture are high compared with other countries of European Union and are mainly due to active agrarian and regional policy of the government. In 1995 almost 45% of farm owners in Federal Republic of Germany had an additional work. In Poland this is a smaller problem (covers 25.7% of farm users). Farmers have extra jobs mostly in industry and building industry. Recently additional work on one's own farm is becoming more significant. It seems that the prospects for multivocationality in agriculture are good and that it is a permanent phenomenon.